Implementing intellectual property rights at universities: Evidence from Vietnam - Anh, Do Thi Van; Huu, Nguyen Duc; Tam, Truong Thi (Edelweiss Applied Science and Technology, 2024)
This article analyzes the current situation of intellectual property rights awareness and implementation in some typical universities of Vietnam. The article analyzes the challenges in the enforcement of intellectual property rights as well as solutions that Vietnam’s higher education system needs to approach to implement in line with international practices. The article synthesizes documents through legal documents of the Vietnamese government on intellectual property rights enforcement. 650 semi-structured survey samples were conducted at 10 major universities in the North, Central and South of Vietnam to survey and collect important information for research purposes. A significant proportion of universities are not really interested in intellectual property rights and intellectual property. Besides, there are certain violations related to copyright in the teaching materials designed in the training program. Enforcement and protection of intellectual property rights is an important tool to bring benefits, such as enhancing the brand of Vietnamese universities. With existing intellectual property, universities need appropriate solutions to enforce current intellectual property rights. The article raises the efficiency and awareness of intellectual property in universities today in Vietnam. By improving the effectiveness of IP rights enforcement in universities, it will create motivation for continuous thinking and creativity, improve competitiveness and bring many benefits and values to the university and society.